(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
The current research is aimed at formulation and in-vivo evaluation of dasatinib solid lipid nanoparticles (SLN) for enhanced solubility and bioavailability. A 33 Box-Behnken design (BBD) was used to optimize the formulations in which amount of glycerol monosterate(X1) the amount of poloxamer 407 (X2) and amount of tyloxopol (X3) were chosen as independent variables while particle size, entrapment efficiency and drug release after 12 hours were chosen as dependent variables. About 17 SLN formulations of dasatinib were prepared using glyceryl monostearate, poloxamer 407, Tyloxopol and Tween 80 and optimised using desirability function. All the SLNs were evaluated for fourier transform infrared spectroscopy (FTIR), particle size, zeta potential, entrapment efficiency and drug release behavior were investigated. The in-vivo pharmacokinetic evaluation of opimised SLN was carried out in rats. Based on BBD and desirability function the formulation comprising of X1:10, X2:06 and X3:02 was chosen optimal. The model was proven to be validated since a fine agreement existed between the predicted and observed results. It can be seen that the experimental values were in very close agreement with the predicted values, indicating the success of the BBD combined with a desirability function for the evaluation and optimization of SLNs formulations. The formulation DF10 displayed a mean particle size of 112 nm with PI of 0.40 and zeta potential of −25.6 mV.The in-vitro release studies showed that more than 98.78% of drug was released from optimized SLN after 12 hours, which is higher when compared with marketed formulation. The release kinetics of the optimized formulation followed zero order drug release and best fitted the Korsemeyer-peppas model. At any time, point, the drug plasma concentrations in animals administrated with optimized SLN was higher than that of pure drug. Cmax of the dasatinib optimised SLN 158.26 ± 0.54 ng/mL was significant (p < 0.05) as compared to the pure drug suspension formulation 32.08 ± 0.21 ng/mL. Tmax of both optimised SLN formulation and pure drug was 1.0 ± 0.47 and 1.0 ± 0.04 hour, respectively AUC0-∞ infinity for dasatinib optimised SLN formulation was higher (702.23 ± 1.26 ng.h/mL) than the pure drug suspension 191.67 ± 1.27 ng.h/mL. Statistically, AUC0-t of the optimised SLN formulation was significantly higher (p < 0.05) as compared to pure drug suspension formulation. These results indicated that the dasatinib-loaded SLN formulation could potentially be exploited for the treatment of chronic myelogenous leukemia with controlled release manner.